KERAMIK TRADISIONAL VERSUS KERAMIK MODERN DI SENTRA GERABAH KASONGAN - Arif Suharson, S.Sn. (Ars: Jurnal Seni Rupa dan Desain, 2007)
Ceramic artists and observers play an important role in the development c f traditional potteryproducts in Kasongan. Pottery products, which were only kitchenwares, have been transformed into bothfunctional and decorative products. Decorative nuance, as the product's characteristic o f this village, ismade by patching technique. Such a technique has made the village o f Kasongan become a famous touristdestination.Foreign demand fo r minimum or eliminated decorative patching has resulted in the disappearance o fthe patching technique. Thus, modern pottery products are combined with such other materials as agel,rattan, stern o f banana bunch, and others.The requirements o f becoming more competitive and obtaining a good market has changed theattitudes of Kasongan people to adjust to ongoing development. This has resulted in the fading o f thetraditional patching technique for the products. This paper is expected to provide further analysis o f theprospects o f Kasongan village development as vxll as an attempt to preserve the patching technique whichused to be a characteristic o f Kasongan pottery.Keywords: Ceramics, Patching technique.